2012
DOI: 10.5194/essdd-5-405-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global marine plankton functional type biomass distributions: <i>Phaeocystis</i> sp.

Abstract: Abstract. The planktonic haptophyte Phaeocystis has been suggested to play a fundamental role in the global biogeochemical cycling of carbon and sulphur, but little is known about its global biomass distribution. We have collected global microscopy data of the genus Phaeocystis and converted abundance data to carbon biomass using species-specific carbon conversion factors. Microscopic counts of single-celled and colonial Phaeocystis were obtained both through the mining of online databases and by accepting dir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…biomass, was recorded during spring (northern hemisphere) with more observations in the month of April compared to March and May, which we also observed in our time-series analysis. Vogt et al (2012) also showed that the minimum and maximum Phaeocystis spp. biomass was between 2.9 Â 10 À5 mg C m À3 and 5.4 Â 10 3 mg C m À3 , with a global mean of 45.7 mg C m À3 for both northern and southern hemispheres, which is similar to the mean at station L4 (41.6 mg C m À3 ).…”
Section: Trends In Phaeocystis Spp Biomass From Time-series Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…biomass, was recorded during spring (northern hemisphere) with more observations in the month of April compared to March and May, which we also observed in our time-series analysis. Vogt et al (2012) also showed that the minimum and maximum Phaeocystis spp. biomass was between 2.9 Â 10 À5 mg C m À3 and 5.4 Â 10 3 mg C m À3 , with a global mean of 45.7 mg C m À3 for both northern and southern hemispheres, which is similar to the mean at station L4 (41.6 mg C m À3 ).…”
Section: Trends In Phaeocystis Spp Biomass From Time-series Analysismentioning
confidence: 91%
“…On a global level, using 5057 observations from 1955 to 2009Vogt et al (2012 showed that 64% of Phaeocystis spp. biomass, was recorded during spring (northern hemisphere) with more observations in the month of April compared to March and May, which we also observed in our time-series analysis.…”
Section: Trends In Phaeocystis Spp Biomass From Time-series Analysismentioning
confidence: 99%
“…The worldwide distribution of Phaeocystis is poorly understood but the locations that it is abundant in have been reported in the Southern Ocean southward of 70°S and in the North Atlantic northward of 50°N [34]. In the coastal upwelling system off Peru, the presence of Phaeocystis globosa has been reported during iron-fertilization experiments [39].…”
Section: Phaeocystismentioning
confidence: 99%
“…This type of information is generally scarce because it requires intense field measurements and laboratory analyses [34]. A first version of a synthetic matrix Rs, containing reference values for PFT, can be obtained from the PHYSAT acceptable ranges of radiance anomalies ( Figure 4) [22,24,27] following the procedure detailed in Appendix B.…”
Section: The Synthetic Matrix Of Typical Nlw Values For Pft Categoriementioning
confidence: 99%
See 1 more Smart Citation